Penerapan Diversi pada Tindak Pidana Pencurian oleh Anak Di Polres Bantul - Suyoto, Devi Mareta; Widowaty, Yeni (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2024)
The increasing number of criminal cases, one of which is the crime of theft, sadly the perpetrators are not only adults but children also have the potential to become perpetrators, this is caused by various factors both internal and external. Law Number 11 of 2012 (UU SPPA) provides an update for the juvenile justice system because it applies the concept of restorative justice, namely through diversion. Seeing this reality raises questions regarding the mechanism for resolving cases through diversion. The purpose of this writing is to find out how the mechanism for resolving criminal cases of theft by children through diversion at the Bantul Police. This study uses a normative research method, namely through literature studies by utilizing secondary data to obtain the information needed, to strengthen the data the author also conducted interviews with the Head of the PPA Unit of the Bantul Police Criminal Investigation Unit Aibda Mustafa Kamal S.H. The results of the study show that the diversion mechanism carried out by the Bantul Police starts from the reported crime, if the perpetrator is a child, diversion will be attempted, the success or failure of diversion is very dependent on the diversion deliberation carried out by the parties involved. In cases handled by the Bantul Police from 2018-2023, there were 11 cases of theft by children, but only 1 case of diversion with a successful status because the ABH and the victim agreed to a form of accountability in the form of compensation (restitution) according to the nominal value of the stolen goods, then the ABH was returned to the parents and as a form of supervision, the Bantul Police enforced mandatory reporting.